Proposed interior design scheme of Saba' Restaurant for Al-Qodwah Sdn Bhd at 20, Ain Arabia, Jalan Sultan Ismail 50250 Kuala Lumpur / Siti Nuratirah Che Mohd Nasir - Che Mohd Nasir, Siti Nuratirah (Faculty of Architecture, Planning and Surveying, 2011)
The project that had been proposed for the final project is to Proposed Interior Design Scheme of Saba’ Restaurant for Al- Qodwah at 20, Ain Arabia, Jalan Sultan Ismail, 50250 Kuala Lumpur. Saba’ Restaurant was well known as Middle Eastern cuisine restaurant since opened in 2007. This proposed new interior design scheme for Saba’ Restaurant is to attract more customer either from Malaysia nor from Middle East tourist since Malaysia Government wants to enhance tourism sector than previous year. The target markets for the customers of this restaurant are for every muslims and especially for middle east muslim tourist in Kuala Lumpur. Concept and image that had been chosen not only must be suitable with the clients as both of it would reflect the client itself. So, the chosen design style for Saba’ Restaurant is Middle East theme with contemporary images. Before getting the design that is suitable with the client’s needs, some data analysis should be done such as the types of customers to attend the session, types of services offer, research and data collection process will be analyzed and applied in the design process to design a comfortable and attractive addition to creating a new image with a touch of style and image of its own.